DAILY WALKING, AUTONOMIC AND CARDIOPULMONARY FUNCTION IN OLDER ADULTS. (16th November 2018) - McCullough, A; Aguiar, E; Moore, C; Amalbert-Birriel, M; Gould, Z; Ducharme, S; Tudor-Locke, C
Abstract: Purpose: To estimate associations between steps/day and prognosticators of morbidity and mortality in community-dwelling 61–85 year-old adults. Methods: Ostensibly healthy older adults [n=13; age: 66(6) years; sex—female: 46%(6), BMI: 26(5) kg/m2] underwent 24-hour free-living walking behavior surveillance for 7 days, as measured by hip-worn triaxial accelerometers. All completed a maximal cardiopulmonary exercise test (CPET) using a modified Balke protocol. Gas exchange was measured via calibrated portable metabolic system, and cardiopulmonary signals were post-processed using a 15-breath moving average filter. Heart rate signals from the first minute of post-exercise recovery were used to calculate the heart rate recovery (HRR) slope (bpm/s). Ventilatory inefficiency (VI) was calculated from the VE/VCO2 slope. Descriptive statistics reported are Median(Interquartile Range) and Frequencies %(n). Associations between anthropometrics, steps/day, HRR, and VI were assessed using a Regression Tree (CART) algorithm, and the leave-one-out-cross-validated root-mean-square-error (RMSE) was calculated. Preliminary Results: Participants wore accelerometers for 7(0) days, 22.5 (1.5) hours/day, and accumulated 9209(3333) steps/day. CPET results showed that HRR was -0.45(0.11) bpm/s and VI was 27.4(8.6), with tests revealing abnormal autonomic (HRR<12bpm) and cardiopulmonary (VI>35.0) function in 8%(1) and 17%(2) of participants, respectively. Higher daily step volumes (>=9300 steps/day) were associated with faster HRR (-0.49 bpm/s) than when fewer steps were taken (-0.38 bpm/s)—RMSE=0.10. Accumulating >=8500 steps/day was associated with better VI (26.2) than when fewer steps were taken (35.1)—RMSE=5.1. Conclusions: Preliminary results suggest associations between autonomic and cardiopulmonary prognosticators of morbidity and mortality and >=9300 and >=8500 steps/day, respectively, in older adults. Funding—NIH-NIA-5R01AG049024.